2019 IEEE SmartWorld, Ubiquitous Intelligence &Amp; Computing, Advanced &Amp; Trusted Computing, Scalable Computing &Amp; Commu 2019
DOI: 10.1109/smartworld-uic-atc-scalcom-iop-sci.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Decision Tree Model of Smoking Behaviour

Abstract: Smoking is considered the cause of many health problems. While most smokers wish to quit smoking, many relapse. In order to support an efficient and timely delivery of intervention for those wishing to quit smoking, it is important to be able to model the smoker's behaviour. This research describes the creation of a combined Control Theory and Decision Tree Model that can learn the smoker's daily routine and predict smoking events. The model structure combines a Control Theory model of smoking with a Bagged De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have identified CTs as a particularly effective method in smoking research [ 63 , 68 , 69 , 70 , 71 ]. CTs are a well-known ML algorithm that uses a tree structure to classify the data.…”
Section: Machine Learning Methods For Auto Intervention: the Future Of Smoking Cessation Appsmentioning
confidence: 99%
“…Several studies have identified CTs as a particularly effective method in smoking research [ 63 , 68 , 69 , 70 , 71 ]. CTs are a well-known ML algorithm that uses a tree structure to classify the data.…”
Section: Machine Learning Methods For Auto Intervention: the Future Of Smoking Cessation Appsmentioning
confidence: 99%
“…Over the past two decades, several studies have been presented regarding this issue. Some of these are given in the following: Classification Trees (CTs) are useful machine-learning algorithms that can be used to classify data on tobacco use, according to the majority of research (Abo-Tabik, Costen, Darby and Benn, 2019;Coughlin, Tegge ,Sheffer, Bickel, 2020;Koslovsky, Swartz,Chan,Leon-Novelo,Wilkinson,Kendzor and Businelle, 2018;Zhang, Liu, Zhang, Huang, 2019). Dumortier, Beckjord, Shiffman and Sejdić, 2016 evaluated the desire to smoke based on 41 characteristics using data gathered from university students.…”
Section: Literature Reviewmentioning
confidence: 99%